A historical perspective on tabloid journalism: The social role of tabloids - Vulić Tatjana; Trajković Jovana (CM. Communication and Media, 2023)
The image of modern journalism increasingly includes tabloidization as an unavoidable process that affects all its aspects. Its influence can be seen as one of the causes of the lowering of professional standards and the overall crisis of the profession and for this reason, tabloid journalism and its social role is the subject of research, with a focus on the press. In this paper, we deal with the history of tabloid journalism, the phenomenology of tabloidization and its impact on the development of journalism. Through a synthetic analysis of current literature, we examine the social status of tabloids, and considering that in academic discussions this type of journalism is generally defined as "bad", we examine to what extent its appearance and actions had positive consequences. In this paper, we will critically review the conflicting positions of world authors, with the aim of determining the social role of tabloids, as well as their influence on the development and functioning of modern journalism. The results of this paper show that it is impossible to interpret the role of tabloids outside of the social, cultural and political environment in which they function. In addition, in the context of social development, the conclusion is implicitly imposed on the necessity of media pluralism in which the audience chooses the content to which it pays attention.